GIS-supported epidemiological analysis on canine Angiostrongylus vasorum and Crenosoma vulpis infections in Germany - Maksimov, Pavlo (Parasit Vectors, 2017)
BACKGROUND: Angiostrongylus vasorum infections are the cause of severe cardiopulmonary diseases in dogs. In the past, canine angiostrongylosis has largely been neglected in Europe, although some recent studies indicated an expansion of historically known endemic areas, a phenomenon that might also apply to Crenosoma vulpis. The aim of the present study was to analyse temporal and spatial trends of canine A. vasorum and C. vulpis infections and to perform GIS-supported risk factor analysis to evaluate the role of landscape, age and seasonality in the life-cycle of these nematodes. METHODS: A total of 12,682 faecal samples from German dogs (collected in 2003–2015) with clinical suspicion for lungworm infection were examined for the presence of A. vasorum and C. vulpis larvae by the Baermann funnel technique and respective epidemiological data (location and age of the sampled dogs, date of sampling) were subjected to GIS-supported risk factor analysis. RESULTS: Overall, A. vasorum and C. vulpis larvae were detected in 288 (2.3%) and 285 (2.2%) faecal samples, respectively. In general, both lungworm infections were found to be widely spread in Germany. GIS-supported analyses demonstrate spatial differences in the occurrence of canine A. vasorum and C. vulpis infections in Germany. also, risk factor analyses revealed an overlap but also diverging risk and protective factors for A. vasorum and C. vulpis infections. The current data also indicate a significant increase of A. vasorum and C. vulpis prevalences from 2003 to 2015 and from 2008 until 2015, respectively, and a potential spread of A. vasorum endemic areas to the northeastern part of Germany. CONCLUSIONS: The results of the present study show an insight into the epidemiological situation of lungworm infections (A. vasorum and C. vulpis) of the past 13 years in Germany. The data clearly demonstrate an increase of diagnosed A. vasorum prevalence in the tested dog population between 2003 and 2015 as well as spatial differences in the occurrence of diagnosed A. vasorum and C. vulpis infections of dogs in Germany. Risk factor analyses suggest possible differences in the biology of these parasites, presumably at the intermediate host level. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-017-2054-3) contains supplementary material, which is available to authorized users.